Preoperative Assessment of Patients Undergoing Bariatric Sleeve Gastrectomy: A Cross-Sectional Study - M. R. Tawfik; N. F. Aldawas; N. S. Almegbil; A. A. Bin Hamad; A. N. Alanazi; A. M. Alaidaroos; T. M. AlRawaf; A. A. Fayed (Gastroenterology Research and Practice)
Introduction. Saudi Arabia (SA) is one of the top countries in the world when it comes to the number of bariatric procedures performed each year. There is still some debate on whether to do regular or selective upper endoscopy during the preoperative examination. The purpose of this study was to explore various endoscopic findings and Helicobacter pylori (HP) infection in symptomatic and asymptomatic patients having laparoscopic sleeve gastrectomy (LSG) prior to surgery. Methods. We investigated a cohort of 132 patients referred to the endoscopy unit from the bariatric surgery outpatient clinic for prebariatric esophagogastroduodenoscopy (EGD) as a part of preoperative LSG. Data extraction from medical records included clinical data such as body mass index (BMI), gastrointestinal symptoms (that include heartburn, regurgitation, epigastric pain, and nausea), medical comorbidities, and laboratory investigations. It included data about the endoscopic findings of EGD procedure as esophageal, gastric, and duodenal findings results as well as the results of biopsy specimens that were taken. Results. Out of 132 patients, 29 (22%) had a BMI of less than 40 kg/m2 whereas 103 (78%) had a BMI of 40 kg/m2 or above, with an average of 44.4±6.4 kg/m2. The average age of participants was 33.6±10.4 years. HP was detected in 36 patients (35.0%) with a slightly greater prevalence in patients with a higher BMI (33.7%) than in patients with lower BMI (35.0%). Collectively, 73 patients (55.7%) had positive endoscopic findings of various grades, sites, and combinations. Incompetent cardia (35.6%) was the most often seen esophageal finding, antral gastritis (34.1%) was the most frequently encountered gastric finding, and duodenitis 1st part was the commonest duodenal endoscopic finding (7.8%). Among asymptomatic patients, incompetent cardia was detected in 33.3%, antral gastritis was found in 30.1%, and around one-quarter of them were positive on HP testing (26.6%). Additionally, 16.1% of them had signs of reflux esophagitis, 17.2% had hiatal hernia, and 14.0% had nodular gastritis. Conclusion. The current study revealed a high prevalence of positive endoscopic findings as well as HP infection upon routine endoscopic examination among patients undergoing bariatric surgery even those who were asymptomatic from any gastrointestinal symptoms.